Tufts Cannon painted to read 'We Believe Dr. Ford' (view from the right) - Mauro, Sari (Tufts Archival Research Center, 2020)
Cannon painted "We Believe Dr. Ford," taken a week after Christine Blasey Ford testified against Supreme Court nominee Brett Kavanaugh in front of the United States Senate.